On the Problem of Colonial Fiction Motives in the English Neo-Victorian Novel - Yuliya Skorokhod’ko (Pitannâ Lìteraturoznavstva)
The article focuses on the neo-Victorian postcolonial novel and on the late neo-Victorian novel with the colonial motives. The article explores genre peculiarities of these modifications of the late neo-Victorian novel. The article focuses on the problem of Britishness as a base of an English identity. ‘British’ features are the peculiar characteristics of any Victorian or modern Englishman. Understanding English national character with its Britishness is a key to the neo-Victorian postcolonial novel and the late neo-Victorian novel with the colonial motives appropriate reading. To achieve the aims of the article the following methods of literary analysis were used: typological, cultural and historical, comparative methods and intertextual analysis. Through the careful analyses of the neo-Victorian novels the author of the article concludes that Victorian colonial novels are the predecessors of the neo-Victorian novels with colonial motives as well as the neo-Victorian postcolonial novels. The basic differences between these varieties of the late neo-Victorian novel are determined by the origin of their author. As the author of the neo-Victorian postcolonial novel originates from the former colonies, such novels focuses on the postcolonial problematics and correspond to the postcolonial canon but not to the neo-Victorian one. On the contrary neo-Victorian novel with the colonial pastiches and parodies Victorian fiction. The prospects of the research include the further exploration of the neo-Victorian postcolonial novel and neo-Victorian novel with the colonial motives.